Flood risk and its reduction in China. (August 2019) - Kundzewicz, ZW; Su, Buda; Wang, Yanjun; Xia, Jun; Huang, Jinlong; Jiang, Tong
Highlights: Floods in China often cause annual loss in excess of 10 billion US. Flood risk has grown in many places in China and is likely to grow further in the future. Floods of a given return period in the reference interval are projected to become more frequent in much of China. There is a strong link between climate variability and abundant humidity in China. Abstract: Despite massive flood protection efforts in China, undertaken since the ancient times, disastrous floods continue to plague the country. In this paper, we discuss changes in flood hazard and flood risk in China. First, we review published results (including our own works) on change detection in observed records of intense precipitation, high river flow and flood damage in China. We provide information on essential features of extreme floods in last decades – floods on large rivers, urban floods, and flash floods. Next, we review available projections for the future (including our own results), related to intense precipitation, high river flow and flood damage in China. We try to interpret the difference in flood hazard projections obtained in various publications. Since the spread of river flood hazard projections is large, projections have to be interpreted with caution, because of the impact on decisions related to climate change adaptation, flood risk reduction, and water resources management. We review flood risk reduction strategies in China, focusing on the present situation and division of responsibilities. China has embarked upon an ambitious and vigorous task to improve flood preparedness, by both structural ("hard") defences, such as: dikes, dams and flood control reservoirs, and diversions, as well as non-structural ("soft") measures: spatial planning and zoning; watershed management (source control), flood forecasting and warning systems; and awareness raising. The strategy of flood mitigation includes flood retention and urban water management to alleviate the burden of flash and urban flooding.